2014
DOI: 10.1021/ja507594h
|View full text |Cite
|
Sign up to set email alerts
|

Tetragonal Phase of 6-Oxoverdazyl Bent-Core Derivatives with Photoinduced Ambipolar Charge Transport and Electrooptical Effects

Abstract: Bent-core mesogens containing 6-oxoverdazyl radical as the angular central unit exhibit rich polymorphism that includes isotropic-isotropic transition, re-entant isotropic (I(re)), and a novel 3D tetragonal (Tet) phases. Surprisingly, the paramagnetic Tet phase interacts linearly with applied electric field and exhibits photoinduced ambipolar charge transport (μ ≈ 10(-3) cm(2) V(-1) s(-1)). Magnetic analysis showed gradual increase of antiferromagnetic interactions upon cooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 35 publications
(54 reference statements)
1
40
1
Order By: Relevance
“…An experimental candidate for which such a piezoelectric coupling plays a role is ref. [13], where it was found that a tetragonal liquid crystalline phase (below two optically isotropic phases at higher temperatures) shows a linear response to an applied electric field. A natural explanation for the behavior observed would be an actual phase sequence isotropic liquid -T d phase -tetragonal phase with octupolar order.…”
Section: The Elastic εT D Phasementioning
confidence: 99%
See 2 more Smart Citations
“…An experimental candidate for which such a piezoelectric coupling plays a role is ref. [13], where it was found that a tetragonal liquid crystalline phase (below two optically isotropic phases at higher temperatures) shows a linear response to an applied electric field. A natural explanation for the behavior observed would be an actual phase sequence isotropic liquid -T d phase -tetragonal phase with octupolar order.…”
Section: The Elastic εT D Phasementioning
confidence: 99%
“…In one case a liquid crystalline tetragonal phase showing a linear electro-optic effect was observed at lower temperatures [13], while in the other three cases Tschierske's group reported the existence of mesoscopic to macroscopic chiral domains of either hand in the lower temperature optically isotropic phase [14][15][16]. This observation was linked to the formation of clusters and or agglomerates of substantial size and associated with steric and packing interactions [14][15][16].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The statics is completed by adding up all the energy contributions ε = ε 0 + ε g + ε l + ε c +ε E , where ε 0 is the part of isotropic liquids andε E describes the influence of external fields (see below). The conjugate quantities then follow from ε as partial derivatives according to (73).…”
Section: Staticsmentioning
confidence: 99%
“…where h is the conjugate to , (73). The stress tensor carries the appropriate counter terms that guarantee zero entropy production.…”
Section: The Non-polar Orthorhombic D2 Tetrahedral Phasementioning
confidence: 99%